Can you identify fake news? Investigating the elements of fake news on social media during the Covid-19 pandemic using the heuristic-systematic model - Foo, Yee Ting; Leong, Jie Rou Sylvine; Liew, Yong Qi; Lim, Zhe Thung; Tan, Suet Yi (2021)
This study is to find out the elements of fake news on social media that persuade young adults to believe in it during the COVID 19 pandemic. The purpose of these findings is to help contribute to the practical and also theoretical significance of similar research to be carried out in the future. The method used for this research is the qualitative research method, where interviews using semi-structured questions will be carried out between the interviewer and the interviewee. A sample size of 25 young adults aged between 19-24 years old, Malaysian citizens and own social media accounts were involved in the current study to answer our research questions of what the elements of fake news on social media are as well as how the elements of fake new persuaded young adults to believe in it during COVID-19 by using purposive sampling method. The findings identified that the four main elements of fake news on social media are the interaction of social media users, visibility, content and influencer. Besides that, the research also revealed the way how the elements of fake news on social media persuade young adults to believe in it during COVID-19. The results showed that the interaction of social media users, visibility, and influencer were proved to confirm the Heuristic-Systematic Model, which states that some people make decisions solely based on non-verbal cues. Hence, this study aims to assist various parties in tackling the issues of fake news as well as educate them with the new knowledge and findings from our research.